Corporate Social and Environmental Responsibility in SOE Mining Sector in Indonesia: Commitment of Social-legal Awareness - Huta Disyon; Widianingsih Widianingsih; Fildzah Rio (JSW (Jurnal Sosiologi Walisongo), 2022)
Through its Corporate Social and Environmental Responsibility (CSER), the company actively contributes to addressing social vulnerability issues in communities. However, when we know that companies are financially impacted, it is interesting to do research on the motivation of companies in providing CSER funds, especially State-Owned Enterprises (SOE), continue to run their CSER programs, whether it is merely an obligation due to regulatory orders or whether there are other motives. This research was conducted from the perspective of the sociology of law. The result shows that the obligation of CSER in several regulations is not merely the lawgiver's desires but comes from social awareness, given that kinship has existed for a long time. Even though there are no explicit restrictions addressing requirements or sanctions to implement CSER in the SOE Law, SOEs in the mining sector demonstrate their commitment to social awareness by continuing to carry out their CSER program in 2020 and 2021.